Synthesis and Biological Activity of Novel Platencin Derivatives - Dennis C. J.Waalboer; Floris P. J.T. Rutjes (Journal of Mathematical and Fundamental Sciences, 2011)
The biological mode of action of platencin, a potential lead molecule for a new class of antibiotics, is detailed. Furthermore, enantiopure syntheses of several platencin derivatives are described, of which the core structure can be accessed in two exceedingly simple steps from commercially available starting materials. Furthermore, the antibiotic properties of the derivatives was evaluated.